Rancang Bangun Bot Pengumuman Di Jurusan Teknik Informatika Universitas Palangka Raya Di Aplikasi Telegram - Pranatawijaya, Viktor Handrianus; Wijaya, Kelvin; Sahay, Abertun Sagit (Journal of Information Technology and Computer Science, 2021)
Announcement is a form of delivering information addressed to the general public. Announcement is a letter addressed to several people, agencies, or other parties whose names are too many to mention one by one. In the announcement in the Department of Informatics, University of Palangka Raya, it still uses a manual system. In a way that is still manual, it takes a lot of time in the process. Like what students have to do, they have to come check the latest announcements, and see new announcements through Whatsapp groups and Telegram groups. Therefore, with this problem, in the process of solving it, an Announcement Bot was made at the Department of Informatics, University of Palangka Raya on the Telegram Application which can complete the completion of finding the latest information by students. The stages of modeling the Announcement Bot in the Department of Informatics, University of Palangka Raya in the Telegram Application using the waterfall research methodology. Where, this methodology has several stages, namely, requirements definition, system and software design, implementation and unit testing, integration and system testing and operation. This Announcement Bot uses the Long Polling method. Where, this method the server will periodically check to the bot whether there is an incoming message. If there is an incoming message, the server will execute based on the request message sent by the user. Testing this system uses a User Acceptance Testing (UAT) testing system. The test results will be used as evidence that the software has been received and has met the requested requirements. This research produces an Announcement Bot at the Department of Informatics, University of Palangka Raya on the Telegram Application that can help find information in the Department for Students.